STOP‐GO MONETARY POLICY. (10th April 2019) - Chappell, Henry W.; Harris, Mark N.; McGregor, Rob Roy; Spencer, Christopher
Abstract : We propose and estimate several discrete choice models of monetary policy decision‐making that feature time‐varying inertia. The models permit us to account for three stylized facts characterizing monetary policymaking in the United States: (1) target interest rates are gradually adjusted in small discrete movements, (2) there are some long stretches of time in which rates are repeatedly moved, and (3) there are other long stretches in which the policy rate does not change. The models are used to account for delayed monetary policy responses to the recession of 2001 and to the housing‐driven expansion of 2003–2006. ( JEL E52, E58, E65)